Intra-ventral tegmental area HIV-1 Tat1–86 attenuates nicotine-mediated locomotor sensitization and alters mesocorticolimbic ERK and CREB signaling in rats - Zhu, Jun; Midde, Narasimha M.; Gomez, Adrian M.; Sun, Wei-Lun; Harrod, Steven B. (Frontiers in Microbiology, 2015)
Cigarette smoking prevalence in the HIV-positive individuals is profoundly higher than that in the HIV-negative individuals. We have demonstrated that HIV-1 transgenic rats exhibit attenuated nicotine-mediated locomotor activity, altered cAMP response element binding protein (CREB) and extracellular regulated kinase (ERK1/2) signaling in the mesocorticolimbic regions. This study investigated the role of HIV-1 Tat protein in the alterations of nicotine-mediated behavior and the signaling pathway observed in the HIV-1 transgenic rats. Rats received bilateral microinjection of recombinant Tat1-86 (25 μg/side) or vehicle directed at ventral tegmental area (VTA) followed by locomotor testing in response to 13 daily intravenous injections of nicotine (0.05 mg/kg, freebase, once/day) or saline. Further, we examined the phosphorylated levels of CREB (pCREB) and ERK1/2 (pERK1/2) in the prefrontal cortex, nucleus accumbens (NAc) and VTA. Tat diminished baseline activity in saline control rats, and attenuated nicotine-induced behavioral sensitization. Following repeated saline injection, the basal levels of pERK1 in the NAc and VTA and pERK2 in VTA were lower in the vehicle control group, relative to the Tat group. After repeated nicotine injection, pERK1 in NAc and VTA and pERK2 in VTA were increased in the vehicle group, but not in the Tat group. Moreover, repeated nicotine injections decreased pCREB in the prefrontal cortex and VTA in the Tat group but not in the vehicle group. Thus, these findings indicate that the direct injection of Tat at the VTA may mediate CREB and ERK activity in response to nicotine-induced locomotor activity.